PERAN RASIO KEUANGAN DALAM MENILAI KINERJA KEUANGAN BANK BCA SYARIAH PERIODE 2018-2021 - Davina Nasywa Ardelia; Fauzatul Laily Nisa (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This research aims to determine the financial ratios at PT Bank BCA Syariah in 2018 - 2021 in the health of Bank BCA Syariah. In this research we use efficiency ratios, then solvency ratios, profitability ratios and liquidity ratios. In this research we use quantitative descriptive research methods through secondary data in financial reports. The results of this research show that financial ratios BCA Syariah bank is stated to be quite healthy on average as measured by the capital adequacy ratio assessment criteria then Return on assets, Return on equality, operational costs and Financing to Deposit Ratio.